Placental cord insertion distance from the placental margin and its association with adverse perinatal outcomes. (December 2020) - Bigelow, Catherine A.; Robles, Brittany N.; Pan, Stephanie; Overbey, Jessica; Robin, Esther; Melamed, Alexander; Bianco, Angela; Mella, Maria Teresa
Highlights: PCI distance from the placental margin is not associated with birth weight. PCI distance from the placental margin is not predictive of fetal growth restriction. Shorter PCI distance from the placental margin is associated with NICU admission. Shorter PCI does not appear to impact rates adverse perinatal or placental outcomes. For patients with a PCI distance <2 cm, reassurance can be provided. Abstract: Objective: The placental cord insertion (PCI) to the placental margin has not been well studied as a continuous variable in relation to birth outcomes. We sought to evaluate the impact of PCI distance on outcomes associated with placental function and development of fetal growth restriction (FGR). Study Design: This was a retrospective study of singleton gestations that underwent a fetal anatomy ultrasound from 2011−2013. The PCI was recorded as the distance in centimeters from the placental margin. Patients had FGR if the overall estimated fetal weight was <10 % for gestational age or abdominal circumference <5 % in the third trimester. Delivery, obstetric, and neonatal outcomes were obtained via medical chart review. Logistic and linear regression models were used to assess the impact of PCI distance on maternal and neonatal delivery outcomes. Results: Of the 1443 women who met inclusion criteria, 93.6 % delivered at term. The mean (±SD) PCI distance was 4.4 ± 1.4 cm. There was no association between PCI and cesarean delivery, peripartum hemorrhage (PPH), pre-eclampsia, 5-min Apgar, or intrauterine fetal demise. PCI distance was statistically significantly shorter in patients requiring neonatal intensive care unit (NICU) admission (4.1 ± 1.5 cm vs. 4.4 ± 1.4 cm, p = 0.02) and was associated with lower birthweight (p = 0.01), though this association was no longer seen when corrected for gestational age. There were 3.5 % of patients who developed FGR; PCI distances from the placental edge were not significantly different for patients who developed FGR compared to those who did not (4.2 ± 1.4 cm vs. 4.5 ± 1.4 cm, p = 0.18). Furthermore, a receiver operating characteristic (ROC) curve for PCI had poor sensitivity (area under the curve [AUC] 0.57, 95 % CI 0.49−0.65). Conclusion: PCI distance at the time of fetal anatomic survey is significantly associated with NICU admission, though does not appear to impact rates of preterm birth, pre-eclampsia, PPH or cesarean delivery. PCI distance in singleton gestations does not appear to be predictive of FGR.